The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4103/2045-9912.184713
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen increases tissue-plasminogen activator-induced thrombolysis in vitro, and reduces ischemic brain damage and edema in rats subjected to thromboembolic brain ischemia

Abstract: Recent data have shown that normobaric oxygen (NBO) increases the catalytic and thrombolytic efficiency of recombinant tissue plasminogen activator (rtPA) in vitro, and is as efficient as rtPA at restoring cerebral blood flow in rats subjected to thromboembolic brain ischemia. Therefore, in the present study, we studied the effects of hyperbaric oxygen (HBO) (i) on rtPA-induced thrombolysis in vitro and (ii) in rats subjected to thromboembolic middle cerebral artery occlusion-induced brain ischemia. HBO increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Four weeks after nerve transection, each group of animals was divided into 2 subgroups: (A) in which rats ( n = 7) were euthanized with an intraperitoneal injection of overdose of sodium pentobarbital, and spinal cord segments of the sciatic nerve removed from vertebral column for biochemical analysis, (B) in which rats ( n = 7) were euthanized with an intraperitoneal injection of overdose of sodium pentobarbital, and spinal cord segments of the sciatic nerve and related dorsal root ganglions (ipsilateral L4 and L5 DRGs) removed for histopathological assessment and immunohistochemistry. The doses and treatment schedules were based on previous studies [ 29 31 ] and pilot experiments in our laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four weeks after nerve transection, each group of animals was divided into 2 subgroups: (A) in which rats ( n = 7) were euthanized with an intraperitoneal injection of overdose of sodium pentobarbital, and spinal cord segments of the sciatic nerve removed from vertebral column for biochemical analysis, (B) in which rats ( n = 7) were euthanized with an intraperitoneal injection of overdose of sodium pentobarbital, and spinal cord segments of the sciatic nerve and related dorsal root ganglions (ipsilateral L4 and L5 DRGs) removed for histopathological assessment and immunohistochemistry. The doses and treatment schedules were based on previous studies [ 29 31 ] and pilot experiments in our laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…The beneficial effects can be attributed to some biological activities such as anti-oxidative [ 21 , 22 ], anti-inflammatory [ 23 , 24 ], and anti-apoptotic [ 25 , 26 ] properties. Also, it was documented that HBO increased oxygen supply [ 27 ] and improved neural metabolism [ 28 ] after ischemia, along with promoting thrombolysis [ 29 ]. Despite the neuroprotective effects of HBO therapy against various experimental models of neural injury and disease, no studies have been conducted on the influence of HBO on neural apoptosis after nerve transection.…”
Section: Introductionmentioning
confidence: 99%
“…Current strategies include the following. (1) Statins may open collaterals after stroke, preserve penumbra, and expand the time window of thrombolysis [ 102 , 103 ]. Ovbiagele et al evaluated the relationship between prestroke statin use and pretreatment angiographic collateral grade among patients with acute ischemic stroke, and they found that the statin-treated group had significantly higher collateral scores than the nonstatin users, suggesting an association between statin use and improved collateralization during acute stroke [ 104 ].…”
Section: Neurovascular Network As Future Therapeutic Targetsmentioning
confidence: 99%
“…It turned out that HBOT increased the thrombolytic effect of r-tPA by 64%, while NBOT only by 39%, as compared to controls. 35 There was also one case report showing a multimodality approach of intravenous and intra-arterial r-tPA thrombolysis repeated HBOT (2.0 ATA, 90 minutes, started 6 hours after stroke onset) and hypothermia improved the symptoms in spinal cord infarction. 36 …”
Section: O-administration Of Hbot and mentioning
confidence: 99%